The Achilles' heel of senescent cells: from transcriptome to senolytic drugs. Issue 4 (22nd April 2015) - Zhu, Yi; Tchkonia, Tamara; Pirtskhalava, Tamar; Gower, Adam C.; Ding, Husheng; Giorgadze, Nino; Palmer, Allyson K.; Ikeno, Yuji; Hubbard, Gene B.; Lenburg, Marc; O'Hara, Steven P.; LaRusso, Nicholas F.; et al.
Summary The healthspan of mice is enhanced by killing senescent cells using a transgenic suicide gene. Achieving the same using small molecules would have a tremendous impact on quality of life and the burden of age‐related chronic diseases. Here, we describe the rationale for identification and validation of a new class of drugs termed senolytics, which selectively kill senescent cells. By transcript analysis, we discovered increased expression of pro‐survival networks in senescent cells, consistent with their established resistance to apoptosis. Using siRNA to silence expression of key nodes of this network, including ephrins (EFNB1 or 3), PI3Kδ, p21, BCL‐xL, or plasminogen‐activated inhibitor‐2, killed senescent cells, but not proliferating or quiescent, differentiated cells. Drugs targeting these same factors selectively killed senescent cells. Dasatinib eliminated senescent human fat cell progenitors, while quercetin was more effective against senescent human endothelial cells and mouse BM‐MSCs. The combination of dasatinib and quercetin was effective in eliminating senescent MEFs. In vivo, this combination reduced senescent cell burden in chronologically aged, radiation‐exposed, and progeroid Ercc1−/Δ mice. In old mice, cardiac function and carotid vascular reactivity were improved 5 days after a single dose. Following irradiation of one limb in mice, a single dose led to improved exercise capacity for at least 7 months following drug treatment. Periodic drug administration extended healthspan in Ercc1−/∆ mice, delaying age‐related symptoms and pathology, osteoporosis, and loss of intervertebral disk proteoglycans. These results demonstrate the feasibility of selectively ablating senescent cells and the efficacy of senolytics for alleviating symptoms of frailty and extending healthspan.